2017
DOI: 10.1074/jbc.m116.773713
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin, a multifunctional cytokine and growth factor, induces leukocyte responses through the integrin Mac-1

Abstract: Pleiotrophin (PTN) is a multifunctional, cationic, glycosaminoglycan-binding cytokine and growth factor involved in numerous physiological and pathological processes, including tissue repair and inflammation-related diseases. PTN has been shown to promote leukocyte responses by inducing their migration and expression of inflammatory cytokines. However, the mechanisms through which PTN mediates these responses remain unclear. Here, we identified the integrin Mac-1 (αMβ2, CD11b/CD18) as the receptor mediating ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 57 publications
2
34
1
Order By: Relevance
“…3C). Similar effects of heparin and anti-Mac-1 function blocking reagents on adhesion of Mac-1-HEK293 cells as well as monocytes have been documented for other Mac-1 ligands (18,19,27), including a multifunctional cationic glycosaminoglycan-binding cytokine and growth factor pleiotrophin (28). These data suggest that on the surface of cells that express HS glycosmanoglycans, HSPGs may serve as co-receptors with Mac-1 to mediate PF4 binding.…”
Section: Figure 7 Effect Of Pf4 On Phagocytosis Of Bacteria and Latesupporting
confidence: 64%
See 1 more Smart Citation
“…3C). Similar effects of heparin and anti-Mac-1 function blocking reagents on adhesion of Mac-1-HEK293 cells as well as monocytes have been documented for other Mac-1 ligands (18,19,27), including a multifunctional cationic glycosaminoglycan-binding cytokine and growth factor pleiotrophin (28). These data suggest that on the surface of cells that express HS glycosmanoglycans, HSPGs may serve as co-receptors with Mac-1 to mediate PF4 binding.…”
Section: Figure 7 Effect Of Pf4 On Phagocytosis Of Bacteria and Latesupporting
confidence: 64%
“…PF4 has a high affinity for heparin (24) and negatively charged proteoglycans (25,26). Furthermore, it is well-known that Mac-1 on monocytes and Mac-1-HEK293 cells cooperates with cell-surface heparan sulfate proteoglycans (HSPGs) during cell adhesion to the extracellular matrix protein CCN1 and to several other Mac-1 ligands (18,19,27,28). To investigate whether HSPGs participate in cell adhesion to PF4, we examined the effect of heparin on adhesion of Mac-1-HEK293 cells.…”
Section: Pf4 Supports Adhesion Of Mac-1-expressing Cellsmentioning
confidence: 99%
“…In the brain, YWHAE is involved in directing the movement of nerve cells by binding to other proteins (Toyo-oka et al, 2003). Pleiotrophin (PTN) plays important roles in cell growth and survival, cell migration, and the expression of inflammatory cytokines (Shen et al, 2017). YWHAE and PTN are mainly expressed in the cerebral cortex (Kido et al, 2014; Shen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotrophin (PTN) plays important roles in cell growth and survival, cell migration, and the expression of inflammatory cytokines (Shen et al, 2017). YWHAE and PTN are mainly expressed in the cerebral cortex (Kido et al, 2014; Shen et al, 2017). POSTN leads to decreased apoptosis during hypoxia (Aukkarasongsup et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Partial inhibition of adhesion by mAb M1/70 suggested that in addition to Mac-1, other structures on the surface of macrophages may be involved in binding to mSIRP␣. To investigate this possibility, we examined whether heparan sulfate and chondroitin sulfate proteoglycans, which commonly cooperate with Mac-1 in adhesion to its ligands (22)(23)(24)(25), are involved in adhesion to SIRP␣. Whereas preincubation of RAW264.7 cells with 10 g/ml of each heparin, chondroitin sulfate A, and chondroitin sulfate B partially inhibited adhesion (35 Ϯ 1, 47 Ϯ 8, and 28 Ϯ 3%, respectively), their combination with mAb M1/70 did not potentiate the inhibitory effect of the mAb (Fig.…”
Section: Sirp␣ Is a Counter-receptor For Integrin Mac-1mentioning
confidence: 99%